2013
DOI: 10.1177/0748233713484654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sugammadex on rocuronium induced changes in pancreatic mast cells

Abstract: Mast cells play a vital role in hypersensitivity reactions. Rocuronium is known to cause mast cell mobilization, hypersensitivity, and pancreatitis. The aim of this study was to investigate the effects of sugammadex on pancreatic changes due to rocuronium. A total of 42 Sprague-Dawley male rats were divided into six equal groups to receive either rocuronium 1 mg/kg intravenously (i.v., R group), rocuronium 1 mg/kg + sugammadex 16 mg/kg i.v. (RS16 group), rocuronium 1 mg/kg + sugammadex 96 mg/kg i.v. (RS96 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…However, there was also one case of a patient in whom sugammadex was not associated with immediate haemodynamic improvement 24 . A potential inhibitory effect of sugammadex on pancreatic mast cells in rats has also been reported 25 .…”
Section: Is Sugammadex Of Benefit In Cases Of Anaphylaxis To Rocuronium?mentioning
confidence: 90%
“…However, there was also one case of a patient in whom sugammadex was not associated with immediate haemodynamic improvement 24 . A potential inhibitory effect of sugammadex on pancreatic mast cells in rats has also been reported 25 .…”
Section: Is Sugammadex Of Benefit In Cases Of Anaphylaxis To Rocuronium?mentioning
confidence: 90%
“…The effects of rocuronium and sugammadex on mast cells and tryptase in liver and pancreas were investigated in rats. 18,19 However, its effects on the lung, one of the important organs affected in anaphylaxis, are unknown. We planned to investigate the changes caused by rocuronium in the lung and the effect of sugammadex on these changes with biochemical, light microscopic, and immunohistochemical parameters on a rat model.…”
Section: Introductionmentioning
confidence: 99%
“…5,24 It has also been reported that ROS play a key role in decreasing immune system defense. 5,24,25 In addition, intense proinflammatory cytokine release, due to excessive ROS formation, has been reported during MTX treatment for cancer and autoimmune diseases. 5,6,24,25 Accumulation of ROS leads to neutrophil infiltration and proinflammatory cytokine release, which triggers apoptosis.…”
Section: A B Cmentioning
confidence: 99%
“…5,24,25 In addition, intense proinflammatory cytokine release, due to excessive ROS formation, has been reported during MTX treatment for cancer and autoimmune diseases. 5,6,24,25 Accumulation of ROS leads to neutrophil infiltration and proinflammatory cytokine release, which triggers apoptosis. 5,6,24,25 Methotrexate is used for the treatment of pancreatic cancer, but has been shown to destroy the beta cells of the pancreas, primarily through oxidative stress.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation